Antibacterial Activity of Quinoline Alkaloids from Cinchona ledgeriana Cell Suspension Cultures Againts Staphylococcus aureus and Escherichia coli - Hasibuan, Yustiny Andaliza; Ratnadewi, Diah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Kina (Cinchona ledgeriana) is a member of the Rubiacea family of the genus Cinchona that contains a secondary metabolite called quinoline alkaloid. In vitro cell culture has been shown to produce secondary metabolites, by cultivating cells in a nutrient-rich liquid medium under suitable environmental conditions. The aim of this study was to determine the antibacterial activity of quinoline alkaloids from Kina cell cultures against Escherichia coli and Staphylococcus aureus. Quinoline alkaloid extracted from Kina cell culture was tested for its antibacterial activity using the well methode. Antibacterial tests revealed that quinoline alkaloids produced greater inhibition zone diameters against S. aureus (7.33 mm) and E. coli (1.66 mm) compared to solutions of pure quinine and quinidine. However, the inhibition of quinoline alkaloids against S. aureus and E. coli was still very low because they only had an inhibition zone with a diameter of <10 m.